A COMPARATIVE STUDY ON THE ENGLISH TEACHING SKILLS BETWEEN THE CERTIFIED AND NON-CERTIFIED ENGLISH TEACHERS IN BANTAENG REGENCY - Dzur Rif'ah Mahmudah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2013)
This study compares the English teaching skills between certified and non-certified English teachers and the endeavors are dominantly done by both in developing the English teaching skills. The causal-comparative design was used to investigate the candidate of Junior and Senior High Schools certified and non-certified English teachers in Bantaeng Regency based on their scores from two standardized instruments. Study result indicated that there was no significant different English teaching skills between certified and non-certified English teachers. In addition, the dominant endeavors done by the certified and non-certified English teachers has revealed that most of certified and non-certified English teachers were active in cognitive stage rather than in practice and evaluation stage. Based on the findings, the researcher deduced that both certified and non-certified English teachers in Bantaeng Regency have no significant difference in the English teaching skills because of both English teachers have similar endeavors in developing their skills.Keywords: English teaching skills, certified English teachers, non-certified English teachers, endeavors, developing skills